Jumping spiders (Araneae: Salticidae) in agroecosystems: a case study to know how friendly some crops can be for native fauna - Rubio, Gonzalo Daniel (2019)
As part of a fragmented landscape, yerba mate and tea are perennial agroecosystems that provide habitat continuity for diverse arthropods. Our objective was to characterize the influence of these two agroecosystems on the native fauna of salticids, measuring the levels of richness, diversity, and density. We hypothesized that the agroecosystems studied do not differ in their capacity to function as reservoirs for the regional fauna of spiders. Each sample comprised suctioning the vegetation in an area of 1 m3 for one minute using a Garden-Vacuum. Twenty-five species of salticids were found. Naubolus posticatus, Chira spinosa, Scopocira histrio and Maeota dichrura were dominant, accounting for more than 20% of the total. Spider densities were similar, 2.21 and 2.47 individuals/m3 in yerba mate and tea. The complexity of the plants was adequate for accommodating several species of salticids. Both crops were also similar in richness and diversity, shared at least 44% of the species, and held more than one fifth of the known richness in the Misiones Atlantic Forest. The discovery of species from an adjacent ecoregion suggests that these crops serve as a reservoir for the fauna and can also act as corridors in the ecotone zone.